ANALISIS KELAYAKAN BUKU CERITA BERGAMBAR BERBASIS KEARIFAN LOKAL DEMAK UNTUK PEMAHAMAN POLA HIDUP SEHAT - Yulita Ayu Suryani; Sri Utaminingsih; Achmad Hilal Madjdi (Jurnal Prakarsa Paedagogia, 2021)
The purpose of this research is to analyze the feasibility of developing a picture book based on local wisdom of Demak. Feasibility is seen from the anatomy aspects of the book, the components of the book content, the intrinsic elements of the book as well as the responses of students and teachers. This research is a quantitative descriptive study. The results showed the feasibility of the book from expert validation obtained a score of 157, mean 4.62 with a percentage of 92% very good category. The results of the student response analysis obtained a score of 4383, a mean of 4.96 with a percentage of 99.2% very good category. The results of the teacher's response obtained a score of 176, the average was 4.51 with a percentage of 90.3% in the very good category. It can be concluded that the picture book based on local wisdom of Demak is suitable to be used for understanding the healthy lifestyle of students.